Results of studying the diabetic retinopathy course in potential kidney and pancreatic recipients while on hemodialysis - I. V. Vorobyeva; E. V. Bulava; A. G. Balkarov; I. V. Dmitriev (Трансплантология (Москва))
Introduction. Kidney and pancreas transplantation is a surgical method for the treatment of patients with diabetes mellitus and terminal diabetic nephropathy. While waiting for surgical treatment, potential recipients receive maintenance hemodialysis. Dialysis initiates the loss of body fluid, which in turn can affect the state of the intraocular structures. Aim. To study the effect of long-term hemodialysis therapy on ophthalmic parameters in patients with terminal diabetic nephropathy. Material and methods. Sixty patients (120 eyes) were examined: group A included 30 patients with end-stage renal failure as a result of diabetic nephropathy, group B included 30 people without systemic and ocular pathologies. The ophthalmological status of group A was assessed at the stage of planned preparation for renal replacement therapy, at 3 and 6 months after the initiation of dialysis. Ophthalmological examination consisted of the use of traditional and special diagnostic methods (microperimetry, photorecording of the fundus, optical coherence tomography angiography). Results. Within 6 months of hemodialysis courses, the following was recorded: a decrease in the thickness of the retina (Me: from 348.5 to 306.1 µm; p <0.05) and choroid (Me: from 330.3 to 294.9 µm; p <0.05), the improvement of retinal perfusion in eyes with diabetic macular edema (Me in the superficial capillary plexus: from 10.6 to 15.8% in the fovea, from 19.7 to 25.4% in the parafovea; in the deep capillary plexus: from 15.4 to 20.9% in the fovea, from 27.5 to 33.5% in the parafovea; p <0.05), a decrease in choroidal hemoperfusion (Me in the layer of choriocapillaries: from 59.0 to 54.2% in the fovea, from 59.3 to 54.7% in the parafovea; in the deep layer of the choroids: from 55.5 to 50.7% in the fovea, from 55.3 to 50.7% in the parafovea; p<0.05),an improvement in retinal photosensitivity (Me: from 16.7 to 20.3 dB in eyes with diabetic macular edema; from 21.1 to 24.2 dB in eyes without diabetic macular edema; p<0.05) and increased visual acuity in eyes with macular edema (Me: 0.1 to 0.3; p<0.05). Conclusions. Against the background of maintenance hemodialysis hemodialysis in patients with terminal diabetic nephropathy, along with a decrease in hyperazotemia, there is an improvement in architectonics, hemodynamics of the retina and visual functions.